NARRATIVE REVIEW: KOMBUCHA'S POTENTIAL AS A RAW MATERIAL FOR HALAL DRUGS AND COSMETICS IN A BIOTECHNOLOGICAL PERSPECTIVE - Firman Rezaldi; Aris Maruf; Fernanda Desmak Pertiwi; Nisa Siti Fatonah; Retna Yulrosly Ningtias; M Fariz Fadillah; Heny Sasmita; Ucu Wandi Somantri (International Journal Mathla’ul Anwar of Halal Issues, 2021)
Kombucha which is efficacious as a source of antioxidants, antibacterial, and anticancer, and alcohol content below 1% deserves to be developed as a raw material for halal drugs and cosmetics in the perspective of biotechnology that underlies the bioinformatics side and gene expression as the initial topic in designing it. The purpose of this review study is to further ensure the feasibility of kombucha as a raw material for halal cosmetics from various supporting scientific findings. The results of the study show that the potential of kombucha as a source of antioxidants, antibacterial, and anticancer agents requires further modification as an opening to prove that it is halal in silico, in vitro, and in vivo from a biotechnology perspective. The development of kombucha as a raw material for halal-standard medicines and cosmetics requires serious research collaboration from biotechnologists engaged in medicine, pharmacy, agriculture, nutrition science, and food technology.